A closer look to the mechanical behavior of the oxide layer in concrete reinforcement corrosion. (1st June 2015) - Sanz, B.; Planas, J.; Sancho, J.M.
Highlights: Accelerated corrosion tests of steel tubes in concrete prisms are reported. Changes in volume and diameter of tube were recorded with special instruments. FEM simulations implementing oxide expansion and concrete cracking agree well. The main crack width is controlled essentially by the net expansion of the oxide. The shear stiffness of the oxide layer does influence the change of shape of the tube. Abstract: Results of concrete cracking in accelerated corrosion tests are presented for concrete prisms cast around a smooth steel tube simulating a rebar. Special instruments were used to measure the variation of inner diameter and volume of the tube while recording the width of the main crack by classical means. Numerical simulations of the tests with a model that reproduces the volumetric expansion of the oxide and the associated concrete cracking were used to narrow the uncertainties in the mechanical properties of the oxide layer with satisfactory results.